Advancing Sustainable Waste Management through National Recycling Rate under SDG 12.5.1 - Muhammad, Gabi Mustapha; Truzsi, Alexandra (International Journal of Engineering and Management Sciences, 2025)
Solid waste management remains a pressing environmental challenge in both developed and developing nations. Recycling has been promoted globally as a key pathway to sustainability, yet recycling rates often provide only a partial picture of performance. In many contexts, challenges such as poorly regulated recycling policies, informal sector dominance, and practices that prioritize profit over environmental sustainability limit progress towards Sustainable Development Goal (SDG) 12.5.1, which tracks the national recycling rate. This study investigates the extent to which recycling rates reflect sustainable waste management and identifies the underlying factors that influence their effectiveness. The major objective of this study is to evaluate recycling rates as an indicator of sustainable waste management. This is further specified by: (i) examining recycling practices in selected countries (Germany, South Korea, USA, Brazil, and India), (ii) identifying key drivers and barriers that influence recycling performance, and (iii) assessing the implications of recycling rates for sustainable waste management systems. The study employed a mixed-methods approach, combining secondary data analysis, comparative country assessment, and policy review. Results show that recycling rates are useful but insufficient as a stand-alone measure of sustainability, since they are influenced by broader elements such as policy enforcement, economic incentives, public participation, and market structures. The findings highlight that Nigeria’s recycling rate remains significantly low compared to leading economies, underscoring the need for integrated waste management reforms. This research contributes to environmental management discourse by demonstrating that while recycling rates provide a benchmark for SDG 12.5.1 monitoring, they must be interpreted alongside contextual drivers to ensure meaningful progress towards sustainable waste management.